STAKEHOLDERS’ PERCEPTION OF THE IMPORTANCE OF DIGITALIZATION IN HEALTHCARE ORGANIZATIONS - Larisa GRIGORIE PATRU (Management & Marketing)
The study aims to identify whether healthcare organizations agree regarding using medical devices involving artificial intelligence and digital technology. Using quantitative research, we collected 123 valid questionnaires from many stakeholders of healthcare organizations (i.e., patients, doctors, nurses, and managers). The results prove that the digitalization process adds value to the decision-making process. Furthermore, the stakeholders perceive digitization as a process that directly contributes to the improvement of the management of healthcare organizations.